The Need Of Implementing More Effective Programs To Reduce Youth Unemployment: The Case Of Slovakia - Dováľová, Gabriela; Hvozdíková, Veronika (European Scientific Journal, ESJ, 2016)
The article illustrates the size of the problem of youth unemployment in Slovakia based on the recent development influenced by the latest crisis. It introduces certain attempts of the economic policy undertaken in Slovakia to tackle this issue. And finally it assesses the efficiency of one of the related ALMP measures – graduate practice program. Young people - generally with less skills and fewer work experience - face serious barriers when entering the labour market in a long-run in Slovakia. Therefore several policy measures were introduced, including so-called ´contribution to graduate practice´ (under § 51 of Act on Employment Services) targeted to enhance employability of graduates by improving their major work-related skills. The cost evaluation of this measure revealed that although it has a certain positive effect on youth employment, it was associated with low efficiency and cost ineffectiveness.